The effectivity of functional drink Keloja in improving nutritional status and immunity of underweight elderly - Pritasari, Pritasari; Ngadiarti, Iskari; Muntikah, Muntikah; Nixon, Aurasyifa Salsabila; Rabbani, Fairuz Dhia (Nutrición Clínica y Dietética Hospitalaria, 2024)
Backgrounds: One of the most common nutritional problems among the elderly population in Indonesia is malnutrition. Malnutrition in the elderly is caused by a decrease in masticatory function, appetite, and digestive system function due to aging. The result of research on the elderly in senior housing shows that 60 percent of the elderly experience malnutrition. Aims: This study aimed to determine the effect of Keloja functional drinks that contained cowpeas, corn, and moringa leaves on the immunity, body weight, and nutritional status of the elderly who were underweight and lived in the South Jakarta Nursing Home. Methods: This study used a quasi-experimental design with 25 samples who met the inclusion criteria. Immunity levels were known by collecting data on CD4, CD8, and the ratio of CD4 and CD8, while body weight and nutritional status data were collected through anthropometric measurements taken before and after the intervention. Results: The results of the analysis showed that there were significant differences in terms of immunity levels, body weight, and nutritional status of the underweight elderly who consumed the Keloja drinks and control groups. However, there were no significant differences in all variables before and after interventions, both in the intervention and control groups. Conclusions: It can be concluded that there was a significant effect of giving Keloja functional drinks on immunity levels, body weights, and nutritional status of the underweight elderly who live in the South Jakarta Nursing Home. For further product development, it is recommended to evaluate the composition of moringa leaves and other ingredients by considering the decline in the digestive tract function of the elderly.